Assessing probability distributions by the fractile method: Evidence from managers - SAMSON, Danny A. (Institutional Knowledge at Singapore Management University, 1986)
Various approaches have been offered as aids for assessing subjective probability distributions. These include the fractile method, the method of relative heights and applications of psychometric methods, e.g. multi-dimensional scaling. Previous laboratory research has examined and compared these methods primarily using undergraduate students rather than relatively experienced or practising managers. In this study of the fractile method, the experimental subjects were managers who had an ongoing instructional relationship with the authors. Therefore, conclusions can be drawn about practising managers' biases in probability assessment. Groups with more expertise in statistics and more managerial experience were found to be better calibrated than those with lower expertise and less experience. Training was also found to improve assessment performance.